ETHANOL EXTRACT AND ACTIVE FRACTION EFFECT OF Moringa Oleifera. Lam IN INHIBITING COX-2 ACTIVITY ON MCF-7 CELL - D, Azizah; K, Masfria; AZH., Poppy (Asian Journal of Pharmaceutical Research and Development, 2018)
The expression of COX-2 is involved in carcinogenesis through the proliferative process, angiogenesis and inhibition of apoptosis. Moringa oleifera has been shown to function as an anti-oxidant, anti-inflammatory, anti-microbial and anticancer. Moringa leaf extraction was done by percolation method, and continued to liquid-liquid extraction to obtain nonpolar, semipolar, and polar fractions using n-hexane and ethylacetate solvent.The aim of this study was to determine the effect of ethanol extract and the fraction of n-Hexane of Moringa oleifera leaf in decreased MCF-7 breast cancer cell and COX-2 expression. This study used true experimentation in vitro design using MCF-7 cells. MTT Assay was performed using a therapeutic dose 6,125-1000 μg / ml to determine IC50 in MCF-7 cells. IC50 of ethanol extract was obtained 94.44 μg / ml and 97.60 μg / ml for n-Hexane fraction. Selectivity index of both samples was 3.95 μg / ml and 2.87 μg / ml. The expression of COX-2 was tested qualitatively with immunocytochemical methods and showed that ethanol extract and n-hexane fraction of Moringa oleifera leaf were able to suppress COX-2 enzyme expression on MCF-7 cells depending on concentration. Keywords: Moringa leaf, cancer cells MCF-7, Apoptosis and COX-2